The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1007/bf02986371
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity testing of heavy metals with theRhizobium-legume symbiosis: High sensitivity to cadmium and arsenic compounds

Abstract: Legume root nodules are the site of biological nitrogen fixation in the Rhizobium-legume symbiosis. Nodules are structures unique to this symbiosis and they are morphologically as well as physiologically distinct from other plant organs. Organic substances affecting the macro- or microsymbionts vitality, such as PAHs (WETZEL: et al., 1991), reduce nodulation even before visible damage to the plant can be detected. We present data that the formation of nodules (nodulation) may also serve for ecotoxicological ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…With this background in mind, the results of this study showed that both As(III) and As(V) were toxic to L. gibba. As(III) species were more toxic than As(V) species (Neumann et al, 1998). However, Knauer et al (1999 reported that As(V) exhibits higher toxicity to algae than does As(III).…”
Section: Relation Of Chemical Speciation To Toxicitymentioning
confidence: 90%
“…With this background in mind, the results of this study showed that both As(III) and As(V) were toxic to L. gibba. As(III) species were more toxic than As(V) species (Neumann et al, 1998). However, Knauer et al (1999 reported that As(V) exhibits higher toxicity to algae than does As(III).…”
Section: Relation Of Chemical Speciation To Toxicitymentioning
confidence: 90%
“…The results demonstrate that processes of plantmicrobe interactions may be very sensitive to HM toxicity and can be disturbed at metal concentrations below threshold toxicity levels determined for each partner separately. It was proposed previously that a high metal sensitivity of symbiosis between alfalfa and S. meliloti may be used as a test to assess the toxicity of soils contaminated with Cd and As (Wetzel and Werner 1995;Neumarnn et al 1998) It is likely that the same test can be created on the basis of symbiosis between pea and R. leguminosarum bv. viciae.…”
Section: Sensitivity Of Symbiosis Between Pea and Nodule Bacteria To mentioning
confidence: 98%
“…The process of nitrogen fixation is sensitive to environmental cues, including the action of heavy metals (Angle et al, 1993;Neumann et al, 1998). Cadmium (Cd) is one of the most toxic elements and plants use different mechanisms to mitigate its toxic effects (Kulaeva and Tsyganov, 2011).…”
Section: Introductionmentioning
confidence: 99%